Towards Human-Centric Mental Health Chatbot Design: Leveraging on DASS-21 - Viola Voon, Li Wei; Tan, Ping Ping; Sim, Chia Wei (Semarak Ilmu Publishing, 2024)
The existing landscape of mental health apps exhibits several limitations, particularly concerning their effectiveness in mental health prevention and their ability to provide adequate assistance for mental health practitioners. In this study, a human-centric design chatbot is proposed leveraging on the Depression Anxiety and Stress Scale 21 (DASS-21) for addressing these challenges. Based on the interviews carried out with five mental health professionals, a chatbot prototype was developed by integrating the DASS-21 assessment tool together with other features aimed at enhancing mental health prevention. The chatbot was then subjected to comprehensive testing involving users and two mental health practitioners. The usability testing with mental health practitioners revealed promising results, indicating that the chatbot effectively supports mental health prevention. Additionally, the feedback from mental health practitioners highlighted the usefulness of the chatbot as a tool in their practice. The usability testing involved 15 university students, with 40.0% female and 60.0% male participants. The majority of respondents were in the age range of 24-26 years old (53.3%), followed by 21-23 years old (40.0%), and a small percentage (6.7%) were 18- 20 years old. In terms of their university year, 86.7% were Year 4 students, and 13.3% were Year 3 students. While most university students expressed agreement with the features in the mobile app, some (13.33%) rated certain aspects as "Average." These included the availability of sufficient information on specific pages and the user interface design, indicating that the chatbot may still be lacking in knowledge, data, and comprehensive functionalities. These findings demonstrate the potential of our human-centric design approach and the integration of DASS-21 within a chatbot framework to enhance mental health prevention. By addressing the limitations of existing mental health apps and garnering positive feedback from users and practitioners, our study contributes to the ongoing efforts in improving mental health support through technology.